Effects of flywheel resistance training on sport actions. A systematic review and meta-analysis - Raya-González J.; Prat-Luri, A.; López-Valenciano, A.; Sabido, R.; Hernández-Davó, J. L. (Journal of Human Kinetics, 2021)
The purpose of the present meta-analysis was to examine the effect of flywheel resistance training (FRT) on main sport action (i.e., jumping performance, sprinting time and change of direction performance) improvements in athletes and healthy active people. A Boolean search strategy adapted for each of the databases employed was conducted to identify all studies measuring change in sport actions performance after FRT interventions up to July 2019. Outcomes were analysed using an average effect size (D+) and a 95% confidence interval (CI), which was calculated assuming a random-effects model. A total of 9 studies with 283 participants met the inclusion criteria and were selected for the analysis. The mean quality score (PEDro scale) of the articles included in the meta-analysis was 5.67. The metaanalysis showed significant positive effects on jumping performance (SMC 0.65; 95% CI, 0.11-1.19; p = 0.02), sprinting time (SMC 1.33; 95% CI, 0.39-2.28; p < 0.01) and change of direction performance (SMC 1.36; 95% CI, 0.58-2.14; p < 0.01) after FRT interventions compared to control/traditional resistance training groups. The results of the present meta-analysis provide evidence of the usefulness of FRT to improve variables related to sport performance in both athletes and healthy population.